Closing the attainment gap in Scottish schools: Three challenges in an unequal society. (March 2017) - McCluskey, Gillean
Scotland's First Minister Nicola Sturgeon has recently said, 'Improving school attainment is arguably the single most important objective in this programme for Government' (Parliamentary address, 1 September 2015). Scotland's levels of academic attainment have become an increasing focus for debate amid continuing concerns that children living in the most deprived areas in Scotland are '6 to 13 months behind their peers in problem-solving at age 5; 11 to 18 months behind their peers in expressive vocabulary at age 5; and around two years of schooling behind their peers at age 15'. The link between educational disadvantage and low levels of attainment is well documented in many countries, but particularly troubling in the United Kingdom, where overall levels of inequality are greater than in many other Organisation for Economic Co-operation and Development countries, including Sweden. This article draws on recent research in three fields of interest, namely student participation, home–school relationships and relationships within school, to explore the challenges for education in improving overall attainment. It considers how these fields of interest connect with each other and with issues of inequality and, finally, argues that they each have the potential to offer a new set of 'guidewires' for tackling this challenge.